Evaluación del efecto de diferentes niveles de suero de leche y el tiempo de fermentación en los indicadores fermentativos de la pulpa de café para uso en la alimentación de rumiantes - Jiménez Montesdeoca, Mónica Rosmeri (2015)
This work was performed at the Laboratory of Food Science within the Agricultural Area of the National University of Loja, in order to establish a protocol for the bio-fermentation of coffee pulp to improve its nutritional value and make it easier to use in animal feed. Four levels of whey (0, 5, 10 and 15%) were assessed over four time periods (0, 24, 48 and 72 hours respectively) using a completely randomized factorial design 4 x 4, resulting in 16 treatments and three repetitions per treatment. 48 Erlenmeyer flasks were used, each constituting an experimental unit. The fermentation was performed in an oven at 36°C, for the time periods set in all treatments and 1.5% urea and 0.5% mineral salts were added to make up the 100g. The variables studied were: chemical composition of the fresh pulp, fermentation indicators (pH and ammonia) and chemical composition of the bio-fermented pulp. The results showed a content of 9.12% crude protein and 16.28% crude fiber for the fresh pulp emanating from the canton of Quilanga; pH levels remained constant during the 72 hours of fermentation; whilst in the 15% treatment, the level was slightly different because it decreased at around 24 hours then increased at 48 hours and finally stabilized at 72 hours. The ammonia content remained constant up to 72 hours, but considerably increased with the treatment levels of 10% and 15% respectively. The dry matter decreased as the fermentation time progressed. The values of ash tended to remain constant; the crude protein reached values of 30.52% with the 15% whey treatment at 48 hours; while the true protein levels reached 9.41% in the treatment of 10% at 24 hours. The crude fiber content increased at 72 hours with the 5% and 10% treatment levels. It was therefore concluded that the fermentation process could increase the protein content of coffee pulp, which in turn facilitated its use as an ingredient in the development of supplementary rations in animal feed.